2008
DOI: 10.1089/hgt.2008.057
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Effects of Tet-on and Mifepristone Inducible Systems in Mouse Liver

Abstract: Control of transgene expression from long-term expression vectors can be achieved with inducible and regulated promoters. The two most commonly used inducible systems employ doxycycline or mifepristone as the drug activating a silent trans-activator, which is expressed from a constitutive promoter. We evaluated the alterations provoked by constitutive expression in the liver of rtTA2 S -M2 (rtTA2; second-generation reverse tetracycline-controlled trans-activator) and GLp65, which are the trans-activators of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A previous report [20] showed that the HD-based procedure allowed for a sustained protein expression over at least 50 days in mice receiving a plasmid containing the human a-1-antitrypsin gene controlled by the same promoter used in this study [18]. In addition, experiments performed by our group showed that DNA transfected into mouse liver by HD injection can be transferred and expressed in about 10-15% of hepatocytes (Reboredo M, unpublished data).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A previous report [20] showed that the HD-based procedure allowed for a sustained protein expression over at least 50 days in mice receiving a plasmid containing the human a-1-antitrypsin gene controlled by the same promoter used in this study [18]. In addition, experiments performed by our group showed that DNA transfected into mouse liver by HD injection can be transferred and expressed in about 10-15% of hepatocytes (Reboredo M, unpublished data).…”
Section: Discussionmentioning
confidence: 59%
“…The hydrodynamics (HD)-based procedure [20] was used to inject mice with 50 lg of plasmid DNA resuspended in 2 ml of saline (0.9% NaCl).…”
Section: Plasmid Construction and Transfection Into Hepatocytes From mentioning
confidence: 99%
“…Although we have not observed significant toxic effects associated with this therapy (Reboredo et al, 2008a), high and persistent levels of IL-12 and its mediator IFNc could result in latent side effects in humans. Therefore, we decided to compare this therapeutic strategy with one that is based on short-term tumor-directed IL-12 expression.…”
Section: Histopathology Of Hccs Developed In Pk/c-myc Transgenic Micementioning
confidence: 58%
“…As a gene switch, the Tet-On system provides a powerful tool to analyze eukaryotic gene expression and function in transgenic mice and gene targeting mouse models (Lottmann et al, 2001;Reboredo et al, 2008). In the Tet-On system, the gene of interest is linked to a tetracycline response element (TRE), which in turn is modified by a reverse tetracycline-dependant transactivator (rtTA) (Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%